AN EMPIRICAL ANALYSIS OF THE IMPACT OF COMPENSATION ON JOB PERFORMANCE AND WORK-FAMILY CONFLICT IN THE KINGDOM OF SAUDI ARABIA-“A CORRELATION MODEL” - Qureshi, Mohammed Owais; Sajjad, Syed Rumaiya (European Scientific Journal, ESJ, 2015)
The purpose of this paper is to find the impact of compensation on job performance and work-family conflict, in the Kingdom of Saudi Arabia and subsequently present a model illustrating a relationship between them. The study is based on primary data collected from 400 employees working in Saudi Arabia. The researchers also do a comprehensive literature review of the past theories and research material available on the specified topic. The illustrated model indicates a relationship between compensation, job performance and work-family conflict by showing the impact of compensation, which is directly and indirectly linked to work-family conflict, through job performance of an employee in the Kingdom of Saudi Arabia. The limitation of the study is that the model is based on data collected from employees working in the Kingdom of Saudi Arabia only, which could have been collected from other regions of the Middle East countries as well. According to this model, compensation to the employees should be paid attention to, which would result in enhanced job performance and conflict free work-family environment.